1996
DOI: 10.1177/002204269602600310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intervention Attrition and Research Attrition on the Evaluation of an HIV Prevention Program

Abstract: Attrition impacts the effectiveness of preventive interventions as well as the external validity of efficacy analyses. This paper examines attrition from the intervention and from the research data collection in an HIV prevention program for out-of-treatment drug users. Of the 1,115 respondents, 87% completed the two-session HIV prevention intervention and of these 69% completed the 6-month data collection. Factors related to completing the intervention were different from those related to completing the 6-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Finally, in contrast to earlier studies (Lauby et al, 1996;Song, Lee, Rotheram-Borus, & Swendeman, 2006), we found that men were less likely to attend the intervention. Workshops were held on both Fridays and Saturdays for men, so it is unlikely that the day of the week can explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Finally, in contrast to earlier studies (Lauby et al, 1996;Song, Lee, Rotheram-Borus, & Swendeman, 2006), we found that men were less likely to attend the intervention. Workshops were held on both Fridays and Saturdays for men, so it is unlikely that the day of the week can explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research investigating the relation between sexual risk behavior and intervention attendance has been mixed (e.g., DiFranceisco et al, 1998;Lauby et al, 1996;Rutledge et al, 2002). Because participants were recruited from an STD clinic and screened into the study based on sexual risk behavior, rates of sexual risk behavior were relatively high, and perhaps we encountered a ceiling effect; that is, rates of sexual behaviors may have been so high in both attendees and non-attendees that we were unable to detect an effect of sexual behavior on workshop attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age, gender, race, substance use, and higher levels of sexual risk behavior have been associated with failure to return for results in HIV testing and counseling (Molitor et al, 1999). In a study on the effects of intervention attrition on the evaluation of an HIV prevention program for adult out-of-treatment drug users, Lauby and colleagues (1996) found that participants who lived alone and did not receive welfare benefits were more like to drop out. Those who ever had an STD or reported needle risk behaviors were more likely to complete the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…While researchers frequently do not report intervention retention rates, those who do have found rates to be as low as 44 Á/54% (El-Bassel et al ., 1995;Kelly et al ., 1994). In the few studies that have specifically examined correlates of low attendance, predictors of attrition have included testing HIV-negative, reporting injection needle risk, or ever having an STD (Lauby et al ., 1996); and perceiving more positive outcomes with condom use, having lower safer sex knowledge, and being younger (DiFranceisco et al ., 1998). In contrast, Kelly et al .…”
Section: Introductionmentioning
confidence: 99%